Type I collagen and fibromodulin enhance the tenogenic phenotype of hASCs and their potential for tendon regeneration - Tian Tu; Yuan Shi; Boya Zhou; Xiaoyu Wang; Wenjie Zhang; Guangdong Zhou; Xiumei Mo; Wenbo Wang; Jinglei Wu; Wei Liu (npj Regenerative Medicine, 2023)
Abstract Our previous work demonstrated the tendon-derived extracellular matrix (ECM) extracts as vital niches to specifically direct mesenchymal stem cells towards tenogenic differentiation. This study aims to further define the effective ECM molecules capable of teno-lineage induction on human adipose-derived stem cells (hASCs) and test their function for tendon engineering. By detecting the teno-markers expression levels in hASCs exposed to various substrate coatings, collagen I (COL1) and fibromodulin (FMOD) were identified to be the key molecules as a combination and further employed to the modification of poly(L-lactide-co-ε-caprolactone) electrospun nanoyarns, which showed advantages in inducting seeded hASCs for teno-lineage specific differentiation. Under dynamic mechanical loading, modified scaffold seeded with hASCs formed neo-tendon in vitro at the histological level and formed better tendon tissue in vivo with mature histology and enhanced mechanical properties. Primary mechanistic investigation with RNA sequencing demonstrated that the inductive mechanism of these two molecules for hASCs tenogenic differentiation was directly correlated with positive regulation of peptidase activity, regulation of cell-substrate adhesion and regulation of cytoskeletal organization. These biological processes were potentially affected by LOC101929398/has-miR-197-3p/TENM4 ceRNA regulation axis. In summary, COL1 and FMOD in combination are the major bioactive molecules in tendon ECM for likely directing tenogenic phenotype of hASCs and certainly valuable for hASCs-based tendon engineering.